A DEVELOPMENT OF INTERACTIVE E-MODULES FOR HIGH SCHOOL PHYSICS LEARNING BASED ON PROBLEM BASED LEARNING (PBL) - Arifin, Imam; Zurweni, Zurweni; Habibi, Ahmad (Indonesian Journal of Educational Development (IJED), 2024)
Interactive multimedia is one factor that can increase student interest and learning outcomes. One of the interactive multimedia is interactive e-modules. The aim of this research is to describe the planning, design and development of learning e-modules, assess the theoretical, conceptual and practical feasibility of interactive e-modules, describe peer responses and describe the attractiveness of interactive e-modules based on Problem Based Learning (PBL). The research method used is Research and Development. The research subjects were students at Ash-Shiddiiqi Jambi IT High School. The development model used as a reference is the Lee and Owen development model, with stages Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The research results showed that the material expert validation results were 97.33% with a very feasible category. And the validation results from media experts were 90.77% in the very feasible category. And the teacher response was obtained with a score of 90.91% in the very appropriate category. Then the one-to-one trial obtained a score of 77.22% in the good category. Next, a small group trial was carried out with a score of 84.73% and a field trial of 89.26%. So interactive e-modules for PBL-based physics learning are suitable for use by SMA IT Ash-Shiddiiqi Jambi students.